Representaciones bisexuales y no binarias en Sex, de Beatriz Gimeno, y Gut Symmetries, de Jeanette Winterson=Bisexual and non-binary representations in Beatriz Gimeno’s Sex and Jeanette Winterson’s Gut Symmetries - León Prieto, Luis (Estudios Humanísticos. Filología, 2019)
Resumen El objetivo de este texto es el de analizar las representaciones bisexuales que existen en Sex, de Beatriz Gimeno, y Gut Symmetries, de Jeanette Winterson, exponiendo los mitos y estereotipos asociados a esta realidad, y mediante una serie de referencias críticas que abordan las teorías queer, el feminismo lésbico y temas como la pornografía o los símbolos fálicos, con figuras como Butler, Wittig, Rich o Preciado, para concluir si estas obras reflejan y en qué modo esta materia. Abstract The aim of this paper is to analyze the representations about bisexuality that are included in Sex, by Beatriz Gimeno, and Gut Symmetries, by Jeanette Winterson, exposing the myths and stereotypes associated with this reality, and through a series of critical references that address the queer theories, lesbian feminism and issues such us pornography or phallic symbols, with figures such as Butler, Wittig, Rich or Preciado, to conclude if this works reflect this matter.